SPOR Festival: 12–15 May 2016 'The Illusionists'. (28th September 2016) - Anderberg, Sune
Abstract : Halfway through Stefan Prins's Mirror Box Extensions (2015) a guy next to me stretches out his arms to hold up an iPad. I've noticed his fiddling with the gadget throughout the performance, lacking the courage to tell him just how distracting it is. As other iPads emerge in the crowd, all of them making noises and projecting tiny details from the stage, I realize I've been tricked. I never figured he was simply following Prins's instructions and was actually participating in this work that focuses on blurring the borders between the virtual and the real.